2005
DOI: 10.1002/eji.200425837
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MHC class I receptors confers functional intraclonal heterogeneity to a reactive expansion of γδ T cells

Abstract: NK cell receptors for MHC class I molecules (MHC-NKR) can be expressed by T cell subsets. The restricted repertoire and phenotypic characteristics of MHC-NKR + T cells indicate that expression of MHC-NKR is acquired upon antigenic challenge and might promote expansion of T cells. Previous studies performed on in vitro generated ab T cell clones concluded that MHC-NKR expression was not a clonal attribute. Here, we examined a massive monoclonal expansion of a non-leukemic cd T cell population found in the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
(44 reference statements)
1
25
0
Order By: Relevance
“…The LES TCR, which directly binds Endothelial Protein C Receptor36, conceivably represents a molecular exemplar of Vδ2 neg adaptive immune surveillance. Naturally expanded during acute CMV infection to∼20% of total T cells, the LES clone was CD28 neg CD45RO neg , suggestive of an effector phenotype40. Also, the LES TCR utilizes a highly complex TCRδ rearrangement (incorporating 14 N/P additions) and a simpler TCRγ chain, typical of many of the Vδ2 neg dominant clonotypes we observed in this study.…”
Section: Discussionmentioning
confidence: 60%
“…The LES TCR, which directly binds Endothelial Protein C Receptor36, conceivably represents a molecular exemplar of Vδ2 neg adaptive immune surveillance. Naturally expanded during acute CMV infection to∼20% of total T cells, the LES clone was CD28 neg CD45RO neg , suggestive of an effector phenotype40. Also, the LES TCR utilizes a highly complex TCRδ rearrangement (incorporating 14 N/P additions) and a simpler TCRγ chain, typical of many of the Vδ2 neg dominant clonotypes we observed in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Because the quality of the signal delivered by CD158 molecules depends on the composition of the intracellular part of the individual receptor or associated molecules, it is difficult to speculate on their precise action; however, these NK receptors may play an important role in the control of T cell activation when the virus persists and coexists with its host for many years [21]. Previously, we showed that CD158j expression confers an enhanced T cell receptor-induced cytotoxic activity to Vd2 neg gd T cells isolated from a CMV-infected kidney transplant recipients, compared with their CD158-negative counterparts [30].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the characteristic TCR, γ δ T cells also possess a variety of NK cell receptors including the activating receptor NKG2D [110], the inhibitory NKG2A, and killer immunoglobulin-like receptors (KIR) [111, 112]; the KIR family of receptors can be activating or inhibitory [113]. NKG2D recognizes the MHC-class I-related molecules MICA and MICB, as well as the UL-16 binding proteins (ULBP), all of which are expressed frequently on transformed cells and deliver activating signals [55, 114].…”
Section: γ δ Recognition Of Tumor Cellsmentioning
confidence: 99%